HUBUNGAN TINGKAT PENGETAHUAN TENTANG KESEHATAN GIGI DAN MULUT DENGAN PERILAKU MENYIKAT GIGI PADA IBU HAMIL YANG BERKUNJUNG DI PUSKESMAS TEGALLALANG I 2022 - Made Sirat; Asep Arifin Senjaya; Nyoman Dewi Supariani; Ni Made Linda Arianti (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
Knowledge is the result of knowing and it occurs after someone senses an object of knowledge. This study aims to determine the relationship between the level of knowledge of dental and oral health and tooth brushing skills in pregnant women who visit the Tegallalang 1 Health Center in 2022. This study is a descriptive study. The results of this study indicate the percentage level of knowledge of pregnant women with good criteria as many as 6 people (20%), enough 19 people (63.3%) and less than 5 people (16.7%). The average level of knowledge of oral health in pregnant women is 68.36 with sufficient criteria. The percentage of teeth brushing skills in pregnant women with very good criteria is five people (16.7%), both 12 people (40%), need guidance as many as 13 people (43.3%) and none with sufficient criteria. The average tooth brushing skill in pregnant women is 67.7 with sufficient criteria. The Spearman Correlation statistical test obtained a probability value of 0.214 which is smaller than 0.05, this means that there is no relationship between the knowledge level of pregnant women and the skills of brushing teeth at the Tegalalang I Health Center. It can be concluded that the percentage level of knowledge of pregnant women about dental and oral health most with sufficient criteria, the average knowledge of pregnant women is sufficient criteria. The percentage of teeth brushing skills in pregnant women is the most with the criteria for needing guidance, the average tooth brushing skills for pregnant women is with sufficient criteria. Analysis with the Spearman Correlation statistical test obtained the results of the probability value of 0.214 which is smaller than 0.05, this means that there is no relationship between the knowledge level of pregnant women and the skills of brushing teeth at the Tegalalang I Health Center.